Association between Health-Related Quality of Life and Medication Adherence in Pulmonary Tuberculosis in South Africa - Kastien-Hilka, Tanja; Rosenkranz, Bernd; Schwenkglenks, Matthias; Bennett, Bryan M.; Sinanovic, Edina (Frontiers in Pharmacology, 2017)
Background: Health-related quality of life (HRQOL) and adherence to treatment are two often inter-related concepts that have implications for patient management and care. Tuberculosis (TB) and its treatment present a major public health concern in South Africa. The study aimed to evaluate the association between HRQOL and adherence in TB patients in South Africa. Methods: Four self-reported HRQOL and one self-reported adherence measures were used in an observational longitudinal multicentre study during six-month standard TB treatment. These included the generic Short-Form 12 items (SF-12) and European Quality of Life 5 dimensions 5 levels (EQ-5D-5L), the disease-specific St. George´s Respiratory Questionnaire (SGRQ) and the condition-specific Hospital Anxiety and Depression Scale (HADS) for HRQOL. Adherence was measured by the Morisky Medication Adherence Scale 8 items (MMAS-8). The relationship between both concepts was examined in 131 patients using Spearman´s rho correlations, and linear regression models. Results: HRQOL improved over six-month TB treatment, whereas adherence mean scores stayed constant with participants attaining a medium average level. Around 76% of patients reported to be high adherers and 24% were reporting a medium or low adherence. Associations between HRQOL and adherence were mainly weak. High adherence at treatment start was positively related to improvements in anxiety and depression after six-month treatment. The overall improvement in pain and discomfort, and psychosocial health aspects over treatment time was positively, but weakly associated with adherence at six months of treatment. Conclusion: A positive relationship exists between adherence and HRQOL in TB in a South African setting, but this relationship was very weak, most likely because HRQOL is affected by a number of different factors and not limited to effects of adherence. Therefore, management of TB patients should, besides adequate drug treatment, address the specific mental and psychosocial needs.